Clinical correlation of brachial artery flow-mediated dilation in patients with systemic sclerosis. Issue 1 (January 2014) - Takahashi, Takehiro; Asano, Yoshihide; Amiya, Eisuke; Hatano, Masaru; Tamaki, Zenshiro; Takata, Munenori; Ozeki, Atsuko; Watanabe, Aya; Kawarasaki, Shuichi; Taniguchi, Takashi; Ichimura, Yohei; Toyama, Tetsuo; et al.
Abstract: Objective To investigate the clinical significance of flow-mediated dilation (FMD) in systemic sclerosis (SSc). Methods Thirty-three SSc patients and 12 healthy controls were studied. Ultrasound assessment of the brachial artery FMD was performed on all subjects. The results were expressed as the percentage of increase in brachial artery diameter following hyperemia. Results Limited cutaneous SSc (lcSSc) patients had significantly lower FMD values than healthy controls (5.3 ± 2.7 versus 7.7 ± 2.0 %, p < 0.05), while the values in diffuse cutaneous SSc (dcSSc) patients (6.7 ± 4.0 %) were comparable to those in lcSSc patients and healthy controls. Although FMD values did not correlate with any clinical features in dcSSc patients, there was an inverse correlation between FMD values and disease duration in lcSSc patients ( r = −0.64, p < 0.05). Furthermore, lcSSc patients with decreased FMD values showed significantly higher prevalence of digital ulcers and elevated right ventricular systolic pressure than those with normal values (for each; 75 versus 10 %, p < 0.05). Conclusion The FMD values represent the severity of vascular damages, which progress along with disease duration and lead to digital ulcers and pulmonary arterial hypertension, in lcSSc patients.